A brief account of the Mechitaristican Society founded on the island of St. Lazaro - Aukerian, Haroutiun, 1774-1854 (My University, 1835)
The Mechitaristican Society (Mekhitarist Congregation) is a Catholic Armenian monastic order founded by Mkhitar of Sebastia in 1701 to promote education and culture. After moving from Constantinople and Greece, the order established its headquarters on the Venetian island of San Lazzaro in 1717, becoming a premier center for Armenian literature, printing, and preservation of manuscripts
[Haroutiun Aukerian]. - Venice : Armenian Acadamy, 1835. - 62 p. ; 18 cm.
Keywords: Mekhitarist Congregation